Pengaruh Persepsi, Motivasi, Minat, dan Kecerdasan Kognitif terhadap Prestasi Belajar Selama Pandemik Covid – 19 Pada Mahasiswa Fakultas Hukum Universitas Prima Indonesia - Nehe, Agustina; Buulele, Rindi Nope Mardelis; Hutabarat, Runggu Ademina; Aruan, Deasy Arisandy; Situmorang, Frenky Nope Mardelis (JOEAI (Journal of Education and Instruction), 2023)
The purpose of conducting this research is to determine the effect of students perceptions, motivation, interest and ognitive intelligence on learning achievement while participating in online learning. Sample in this study namely students of the Faculty of Law, Prima Indonesia University, totaling 200 people. The analytical method used in this study is the quantitative method. The data collection technique is using questionnaires through the Google form. Data analysis technique using purposive sampling from research showed that Variabel Perception (X1), Motivation (X2), Interest (X3) and Intelligence cognitive (X4) has a Positive significant effect on variabel Achievement Learning (Y). Then can be concluded that The effect of on each variabel simultaneously. an be seen that value Fcount (194.974 > 2.41796) or sig.. 0.000 < 0.05. Keywords: Kognitive Intelligence, Interest, Learning Achievement Motivation, Perception